WRNIP1: A new guardian of genome integrity at stalled replication forks. (2nd September 2016) - Leuzzi, Giuseppe; Marabitti, Veronica; Pichierri, Pietro; Franchitto, Annapaola
ABSTRACT: Failure to protect and/or restart stalled replication forks contributes to genomic instability. Radiation-sensitive 51 (RAD51) recombinase defends stalled forks from nucleolytic attack, which otherwise can threaten their integrity. Recently, we have uncovered a novel and key function of Werner helicase interacting protein 1 (WRNIP1) as a fork-protective factor working in conjunction with RAD51 in response to replication stress.